Teaching English as an International Language (TEIL) in the ELT Curriculum: A Library Research - Suci Indah Sari; Riska Rahma dani; Aidil Syah Putra (Universitas Nurul Jadid, 2026)
The global spread of English has significantly reshaped the goals and practices of English language teaching worldwide. English is no longer used exclusively by native speakers but functions as an international language for communication among speakers from diverse linguistic and cultural backgrounds. This development has led to the emergence of Teaching English as an International Language (TEIL), which emphasizes intelligibility, communicative effectiveness, and intercultural awareness rather than native-speaker norms. This study aims to examine the concept of TEIL and its implications for the development of the English Language Teaching (ELT) curriculum. Employing a qualitative approach with a library research design, this study analyzes fifteen relevant national and international journal articles using content analysis techniques. The findings reveal that the integration of TEIL principles into the ELT curriculum supports the development of global communicative competence, acceptance of English language variation, and cross-cultural understanding. The review also indicates that teachers and students generally hold positive perceptions of the TEIL approach, although challenges remain in terms of teacher readiness and the availability of appropriate teaching materials. Overall, the study highlights the importance of adopting a TEIL-oriented ELT curriculum to create more inclusive, contextual, and globally relevant English language education.